Nasopharyngeal and Oropharyngeal Colonization by Staphylococcus aureus and Streptococcus pneumoniaeand Prognostic Markers in Children with Sickle Cell Disease from the Northeast of Brazil - Rocha, Larissa Carneiro (2017)
Brazilian National Council of Research (CNPq) (311888/2013-5) (MdSG); the Foundation Research and Extension of Bahia (FAPESB) (3626/2013, 1431040053063, and 9073/2007) (MdSG); and PPSUS/FAPESB (020/2013 EFP-00007295), (MdSG); the Instituto Nacional de Ciência e Tecnologia do Sangue (CNPq) (Coordinated by S.T.O.S.), and MCD/CNPq/MS-SCTIE-DECIT (409800/2006-6), (MdSG